Straightforward Synthesis of 3-Selenocyanato-Substituted Chromones through Electrophilic Selenocyanation of Enaminones under Grinding Conditions - Xiao, Jun-An; Cheng, Xiu-Liang; Meng, Ru-Fang; Qin, Xiao-Shi; Peng, Hai; Ren, Ji-Wei; Xie, Zhen-Zhen; Cui, Jian-Guo; Huang, Yan-Min (Synthesis, 2020)
A metal- and oxidant-free method for preparing 3-selenocyanato-substituted chromones from 2-hydroxyphenyl enaminones by using a newly developed electrophilic selenocyanating reagent is reported. A series of 3-selenocyanato- or 3-thiocyanato-substituted chromones, as well as 3-selenocyanato- or 3-thiocyanato-substituted quinolinones was obtained in good to excellent yields under grinding reaction conditions. The generality and utility of this approach were demonstrated by a scale-up reaction and transformations of one of the products.
Keywords: selenocyanation; chromones; grinding; organoselenium compounds; solvent-free conditions